An analysis of the effectiveness of the use of prepaid meters as a revenue management tool: a case study of Zimbabwe Electricity Transmission and Distribution Company ( ZETDC) (2012-2014) - Chirewo, Rumbidzai (Midlands State University, 2018)
This research study is designed to make a sound investigation into the use of prepaid meters by Zimbabwe Electricity Transmission and Distribution Company as a revenue management tool. The nature of the research aimed in identifying and evaluating the revenue management policy of the company in place, the implementation guidelines and personnel capabilities, challenges being faced in the revenue management, controls that have been put in place over revenue management and coming up with the best practice for revenue management of the company. The research was conducted using the descriptive method and the stratified random sampling technique. Questionnaires and interviews were used to obtain and collect data. Primary and secondary data was obtained that relates to the nature of the research study and combined findings were presented by the use of charts, graphs and tables. Data analysis was done using the mean, mode and median. Summaries of every chapter, conclusions and recommendations were also presented.